Prognostic impact of right ventricular function in advanced heart failure. (4th February 2022) - Dias Ferreira Reis, JP; Bras, P; Goncalves, A; Pereira Da Silva, T; Soares, R; Galrinho, A; Timoteo, AT; Branco, L; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction In patients with heart failure with reduced ejection fraction (HFrEF), the presence of coexistent right ventricular (RV) systolic dysfunction is associated with a worse functional capacity and outcome. However, the measurement of RV function is often overshadowed by its left counterpart. Purpose To assess the prognostic impact of RV dysfunction in a population of advanced HF patients. Methods Prospective evaluation of adult patients with advanced HFrEF referred to our Institution for evaluation with HF team for possible indication for urgent heart transplantation (HT) or MCS. Patients were followed up for 1 year for the primary endpoint of cardiac death and HT. RV systolic dysfunction was defined by a tricuspid annular plane systolic excursion (TAPSE) < 17 mm and/ or fractional area change (FAC) < 35%. A survival analysis was performed to evaluate the prognostic impact of RV dysfunction and survival curves were compared using the log-rank test. Results A total of 450 HFrEF patients (mean age of 56 ± 12 years, 80% male, mean LVEF of 29 ± 4%, mean TAPSE of 19 ± 3 mm and RV FAC of 37 ± 6%), of which 30.4% had RV dysfunction. Thirty patients (6.7%) met the primary endpoint. Patients with RV dysfunction had a higher NT-proBNP value (3278.9 ± 296.7 pg/mL, p = 0.005) and a lower LVEF (26.7 ± 6.4 vs 31.4 ± 5.1, p < 0.001), as well as a worse cardiopulmonary fitness (CPET duration: 7.2 ± 3.8 vs 8.6 ± 4.1, p = 0.019; pVO2: 13.6 ± 4.9 vs 16.2 ± 6.1 ml/kg/min, p = 0.006; VE/VCO2 slope: 41.8 ± 11.9 vs 37.0 ± 10.6, p = 0.015; cardiorespiratory optimal point: 33.0 ± 8.9 vs 28.4 ± 6.2, p < 0.001). RV dysfunction was associated with a lower survival free of events during the first follow-up year (log-rank p = 0.046). Conclusion: RV is associated with a poor survival in advanced HF patients and it may improve risk stratification in this population.